Laboratory experiments of various bio-asphalt on rheological and microscopic properties. (20th October 2021) - Lv, Songtao; Liu, Jing; Peng, Xinghai; Jiang, Meng
Abstract: Bio-oil is widely used to prepare bio-asphalt, which has attracted more and more attention. However, bio-asphalt performance is different for bio-oil is various, so it is challenging to have a unified standard evaluation. In order to investigate the characteristics of various kinds of bio-asphalt, this paper used five bio-oils (vegetable oil, soybean oil, castor oil, straw oil, waste oil) to modify the neat asphalt. Meanwhile, the rock asphalt was selected to modify the bio-asphalt, and its content is 5% by weight of the neat asphalt. By testing the rheological performance of rock asphalt modified bio-asphalt, the modification effects of different bio-oils were compared, and the advantages and disadvantages of different bio-oils were analyzed and compared. Finally, through Fourier transform infrared spectroscopy (FTIR) test and scanning electron microscope (SEM), the mechanism of bio-oil and rock asphalt composite modified neat asphalt was studied. The test results show that the rheological properties of different rock asphalt modified bio-asphalt are intensely different. Also, the infrared spectra of bio-oils from different sources are extremely different. There is no obvious correspondence between the infrared spectra of bio-oils and the macro performance of bio-asphalts. Besides, neat asphalt, bio-oil, and rock asphalt have favorable mixing compatibility. This paper determines the applied situations of various bio-oil and evaluates the modification effect of different types of bio-oil on neat asphalt. At the same time, this work reveals the modification mechanism of rock asphalt modified bio-asphalt, which provides a basis for future bio-asphalt application. Highlights: Bio-asphalts from different bio-oil sources were prepared. Different kinds of bio-oil have individual rheological properties. The interaction mechanism between rock asphalt and various bio-asphalts was revealed.